2011
DOI: 10.2131/jts.36.135
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to arsenite induces S100A8 and S100A9 expression in rat RBL-2H3 mast cells

Abstract: -To investigate the effects of chronic exposure to arsenite on the gene expression proto arsenite for 28 days. Upregulated genes include calcium-binding S100 proteins such as S100A9, S100A10, S100A6, and S100A13, and granzymes B and C. Among S100 proteins, S100A9 showed the highest expression (8.62-fold of untreated cells) after 4-weeks of exposure to arsenite. As S100A8 and S100A9 comprise a heterodimer called calprotectin, and are implicated in the development of atherosclerosis and cancer, mRNA levels of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We previously showed that expression of S100A8 and S100A9 is upregulated by chronic exposure to As(III) in rat RBL-2H3 cells (6). In the present study, we first examined whether As(III) also induces S100A8 and S100A9 expression in other human-derived cell lines, including lung epithelial A549 cells, kidney carcinoma Caki-2 cells, immortalized skin keratinocytic HaCaT cells, embryonic kidney HEK293 cells, liver carcinoma HepG2 cells, immortalized T lymphocyte Jurkat cells, normal human epidermal keratinocytes (NHEK), leukemic monocyte lymphoma U937 cells, and immortalized bladder urothelial UROtsa cells.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…We previously showed that expression of S100A8 and S100A9 is upregulated by chronic exposure to As(III) in rat RBL-2H3 cells (6). In the present study, we first examined whether As(III) also induces S100A8 and S100A9 expression in other human-derived cell lines, including lung epithelial A549 cells, kidney carcinoma Caki-2 cells, immortalized skin keratinocytic HaCaT cells, embryonic kidney HEK293 cells, liver carcinoma HepG2 cells, immortalized T lymphocyte Jurkat cells, normal human epidermal keratinocytes (NHEK), leukemic monocyte lymphoma U937 cells, and immortalized bladder urothelial UROtsa cells.…”
Section: Resultsmentioning
confidence: 98%
“…We previously showed that S100A8 and S100A9 are upregulated in rat RBL-2H3 mast cells after chronic exposure to As(III) (6). To test whether this induction is restricted to RBL-2H3 cells, nine human-derived cell lines were exposed to As(III).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100a9, which encodes the S100A9 protein, was also ranked as having the third-lowest expression in both RBL-Mnr300 and RBL-Mnr1200 cells ( Supplementary Table 2). S100 family proteins commonly contain EF-hands for calcium-binding in their protein structure, and are involved in a variety of immunological responses (Shimizu et al, 2011;Foell et al, 2007;Marenholz et al, 2004).…”
Section: Resultsmentioning
confidence: 99%